2021
DOI: 10.3389/fpubh.2021.650022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fibroblast Activation in Uterine Leiomyoma by Components of Rhizoma Curcumae and Rhizoma Sparganii

Abstract: Background: The herbs Rhizoma Curcumae and Rhizoma Sparganii (RCRS) are often used in traditional Chinese medicine for the treatment of uterine leiomyoma (UL). The effectiveness of RCRS for the treatment of UL has been confirmed in our previous studies.Purpose: This study aimed to investigate the molecular mechanism by which RCRS inhibits the activation of fibroblast activation protein (FAP) and prevents UL in rats.Study Design and Methods: A Sprague Dawley (SD) rat model of UL was established via estrogen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Curcumin, another natural substance with proven therapeutic effects on UFs, can reduce oxidative stress and protect against inflammation in leiomyoma. Its action is expressed through modulation of pro-inflammatory cytokines and signaling pathways, including peroxisome proliferatoractivated receptor-gamma (PPAR-γ) [105,[107][108][109][110].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin, another natural substance with proven therapeutic effects on UFs, can reduce oxidative stress and protect against inflammation in leiomyoma. Its action is expressed through modulation of pro-inflammatory cytokines and signaling pathways, including peroxisome proliferatoractivated receptor-gamma (PPAR-γ) [105,[107][108][109][110].…”
Section: Discussionmentioning
confidence: 99%
“…Tsuiji et al noted the effect of curcumin on peroxisome proliferator-activated receptor-gamma (PPARγ) activation [108]. Feng et al demonstrated in an animal model that Rhizoma Curcumae (RC) and Rhizoma Sparganii (RS), used in traditional Chinese medicine, were effective in preventing and treating UFs in rats [109]. The combination of RC and RS effectively reduced the expression of extracellular matrix component collagen, fibroblast activating protein, and transforming growth factor beta (TGF-β), simultaneously decreasing the expression level of signaling factors (AKT, ERK and MEK) in cell proliferation [109].…”
Section: Curcumin/turmericmentioning
confidence: 99%
“…Moreover, CRSR was found to affect various ECM-associated genes, which may be responsible for its ability to decrease uterine mass ( Yu et al, 2019 ). In line with the hypothesis that CRSR produces an effect on the ECM, another independent study reported a reduced expression of fibroblast activation protein, which is a collagen component of the ECM and TGF-b ( Feng et al, 2021 ).…”
Section: Polyherbal Formulation For Uterine Fibroidsmentioning
confidence: 74%
“…At present, there are many studies, and the outstanding curative effect of zedoary tumeric in liver cancer has also been confirmed. Some active components, including curcumol, zedoarondiol, curcumenol, curdione, curcumin, germacrone β-elemene, have been proved to exist in a large number in zedoary tumeric ( Gao et al, 2017 , Chen et al, 2008 , Xu et al, 2015 , Matsuda et al, 1998 , Lou et al, 2009 ), and it has also been reported that these components have significant anticancer activity ( Mao et al, 2013 , Pan et al, 2018 , Ahmed Hamdi et al, 2014 , Zeng et al, 2012 , Feng et al, 2021 ), and these components have been identified as quality markers of liver protection and anticancer of zedoary tumeric ( Li, Cao, & Hao, 2021 ). The research idea of this paper is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%